21st Century Homeopathy - Bannan, Robert (Homœopathic Links, 2014)
Four years of experience with the algorithm method. Algorithm – an entirely different approach to finding correspondence between substances and people. It does not make any reference to signs or symptoms at all. Therefore it bypasses most of the problems inherent in our repertories. It is also a lot quicker than repertory work.
Keywords: Candegabe algorithm or the HUMA method; Numero-phonetic code; International phonetic alphabet; Homeopathic materia medica; Symmetry; Anthrokokali; Plutonium nitricum